The cross-section of labor leverage and equity returns - Andres Donangelo; François Gourio; Matthias Kehrig; Miguel Palacios (Federal Reserve Bank of Chicago, 2017)
Using a standard production model, we demonstrate theoretically that, even if labor is fully flexible, it generates a form of operating leverage if (a) wages are smoother than productivity and (b) the capital-labor elasticity of substitution is strictly less than one. Our model supports using labor share - the ratio of labor expenses to value added - as a proxy for labor leverage. We show evidence for conditions (a) and (b), and we demonstrate the economic significance of labor leverage: High labor-share firms have operating profits that are more sensitive to shocks, and they have higher expected asset returns.
Keywords: 330; Arbeitskosten; Produktionstheorie; Kapitalmarktrendite; Theorie